Pembentukkan dan Pengembangan Karakter dalam Kepemimpinan - Lisdawati Muda (Al-Ulum, 2014)
Leaders are individuals who led a social activity. They should regulate, lead, organize, manage and evaluating people. Therefore, leadership should have a legitimate acknowledgment and support from his followers. In order to have a great deal of influence from his/her followers, a leader should have good personality and good character; that is, understand and aware his/her own existences, respect to others, have good morality and also devout to Allah SWT. To develop a good and strong leadership, a leader should have spiritual and emotional intelligence and develop these intelligences continually, so his/her good character eventually will be built and it will be useful for his/her organization and community.